Laying foundation of a successful social enterprise: case study of Junior Chamber International (JCI) Lipa’s Project GANAP - Resurreccion, Analiza D. (International Multidisciplinary Research Journal, 2020)
This case study underscores the significance of the different livelihood assets including human capital, financial capital, natural capital, physical capital, and social capital in the initiation phase of Junior Chamber International (JCI) Lipa’s Gawaing Nagpapaunlad ng Pangkabuhayan or Project GANAP. These assets were tagged necessary in the pursuit of positive livelihood outcome that is to uplift the lives of the families in Sitio Hillview in Lipa City, Batangas. In- depth interviews with JCI Lipa key persons and focus group discussion with women participants were conducted by the researcher to determine how the aforementioned livelihood assets were utilized by JCI Lipa. Gathered data revealed that utilization of the livelihood assets is subject to some vulnerabilities, thus sustainability efforts are paramount.. The researcher recommends that since livelihood assets potentially affect the use of other livelihood assets and effective utilization, thus, a study on the mutual impact of these assets not just with Project GANAP but with other governmental and non- governmental social enterprise initiatives be pursued in the future research.